Material Selection with Value Engineering Technique- A Case Study in Construction Industry - UĞURAL, MEHMET NURETTİN (University of Osijek, 2023)
As a result of the rising level of competition in the construction industry, businesses strive to stay one step ahead of their rivals and overcome the most fundamental optimization challenge of balancing quality, time, and cost parameters. This is not always possible, however. Occasionally, the project may be completed late, the budget may be exceeded, or the desired quality cannot be attained. Various strategies have been developed to address these issues. The value engineering method is among these techniques. Taking into account quality, time, and cost, value engineering executes cost-saving projects without disregarding customer expectations. Value engineering seeks to increase value by concentrating on functions other than cost management. By conducting value studies on the products, value engineering can introduce new designs, develop the existing product, or provide value to the customer. This study employed value engineering to determine the thermal insulation material to be used in a building. First, the functions to be worked on were determined by considering user expectations, and then three alternative products that provide these functions were identified among the most preferred products. By developing alternative products, the advantages and disadvantages of the original products were revealed. The most valuable product was determined by calculating the product's value in relation to its benefits and costs. Thus, the optimal product was selected by weighing the user's expectations, the product's benefits, and its price.
Keywords: Civil Engineering; Project Management; Value Engineering